GAYA BAHASA METAFORA DALAM PEMBERITAAN PANDEMI COVID-19 - Yashinta Intan Aprilia (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2022)
Language application this day is having a lot development, especially in pandemic covid-19 situation this day, word development an the meaning is occur in some term that strange and unique even the term is never being used before, No exception in covid-19 phenomena that include a new term, This research is using describtive way and studying some new terms in pandemic covid-19, language application with metaphore way or the meaning of word with not the real meaning of it, This research is beneficial for improving knowledge about what is metaphore for both writer and reader. Keywords: Metaphore, Covid-19, Term